Prognostic role of fibrinogen-to-albumin ratio in patients with gynecological cancers: a meta-analysis - Chen, Yaping; Zhang, Jiliang (Frontiers in Oncology, 2025)
BackgroundFibrinogen-to-albumin ratio (FAR) has been widely studied for its prognostic value in gynecological cancers, but the results remain inconsistent. Therefore, this study aimed to evaluate the precise prognostic significance of FAR in gynecological cancers.MethodsA comprehensive literature search was conducted in PubMed, Web of Science, Embase, the Cochrane Library, and China National Knowledge Infrastructure (CNKI) databases up to 12 May 2025. The prognostic value of FAR for overall survival (OS) and progression-free survival (PFS) in gynecological cancers was examined using pooled hazard ratios (HRs) and corresponding 95% confidence intervals (CIs).ResultsA total of 10 articles comprising 1,902 patients were included in this meta-analysis. Pooled results indicated that elevated FAR was significantly associated with poor OS (HR = 2.75, 95% CI: 2.26–3.36, p < 0.001) and shorter PFS (HR = 1.60, 95% CI: 1.20–2.12, p = 0.001) in patients with gynecological cancers. Subgroup analyses confirmed that FAR predicted OS regardless of sample size, cancer type, FIGO stage, treatment modality, FAR threshold, threshold determination method, or type of survival analysis (p < 0.05). Additionally, FAR remained a significant predictor of poor PFS across different cancer types.ConclusionThis meta-analysis showed that a high FAR is significantly associated with worse OS and PFS in patients with gynecological cancers. FAR may serve as a promising prognostic biomarker in clinical practice.Systematic review registrationhttps://inplasy.com/inplasy-2025-5-0036/, identifier INPLASY202550036.